Bedömnings-, dokumentationspraktiker och pedagogiska identiteter - Andreasson, Ingela; Asplund Carlsson, Maj; Dovemark, Marianne (Educare, 2015)
When competition and an increasing level of marketisation characterises school life, the number of evaluations and the level of control has grown out of proportion. Through comparisons, assessments and ranking systems, also called ‘the terrors of performativity’ according to Ball (2003) commercial agents have gained influence over practices of assessment and documentation within the education system. Increased demands on pupils’ and parents’ participation and a belief that written documentation will lead to better results has caused an extensive use of different web based tools like Unikum. With the point of departure in a collected material of more than a hundred Individual Educations Plans (IEP) where commercial web based tools have been used, we make an analysis with Basil Bernstein’s (1996, 2000) concepts Pedagogic Identity, and Instructional and Regulative discourse in relation to expectations and constructions manifest in the plans. The results show that all four identities are expressed in the plans however, with an emphasis on a neo-liberal identity. We discuss the results in relation to the instructional and regulative discourses. The conclusion is that the tools both shape and determine possible identities and possible discourses in the web based interaction between children, parents and teachers.